2022
DOI: 10.1007/s12552-022-09372-5
|View full text |Cite
|
Sign up to set email alerts
|

Local TV News Coverage of Racial Disparities in COVID-19 During the First Wave of the Pandemic, March–June 2020

Abstract: The COVID-19 pandemic has disproportionately impacted health and social outcomes for people of color in the United States. This study examined how local TV news stories attributed causes and solutions for COVID-19-related racial health and social disparities, and whether coverage of such disparities changed after George Floyd’s murder, during the first wave of the COVID-19 pandemic. We systematically validated keywords to extract relevant news content and conducted a content analysis of 169 discrete local TV n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…This difference also suggests that left-populated outlets and centralists inform the public of "new normal" in the endemic phase by specifically highlighting the economic consequences and social value of improving the quality of life of citizens. Previous studies have reported that pandemic news coverage induced negative sentiment (Aslam et al, 2020;Iwendi et al, 2022) and was dominated by political actors (Leidecker-Sandmann et al, 2022;Xu et al, 2022). The characterisation of connections between the nature of science categories provides a more objective and sophisticated indicator of how two aspects of scientific works were addressed in reporting public healthcare crises.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference also suggests that left-populated outlets and centralists inform the public of "new normal" in the endemic phase by specifically highlighting the economic consequences and social value of improving the quality of life of citizens. Previous studies have reported that pandemic news coverage induced negative sentiment (Aslam et al, 2020;Iwendi et al, 2022) and was dominated by political actors (Leidecker-Sandmann et al, 2022;Xu et al, 2022). The characterisation of connections between the nature of science categories provides a more objective and sophisticated indicator of how two aspects of scientific works were addressed in reporting public healthcare crises.…”
Section: Discussionmentioning
confidence: 99%
“…In their framework, the nature of science is viewed as comprising a social-institutional system and a cognitive-epistemic system: for the social-institutional system, it encompasses how scientific knowledge is shaped by the social and political dimensions, namely social certification and dissemination, social values, scientific ethos, professional activities, social organisations and interactions, financial systems and political power structures; for the cognitive-epistemic system, it describes scientific practices of enquiry, aims and values, methods and methodology rules, and forms of scientific knowledge. A majority of previous studies, which were conducted at the beginning of the Covid-19 pandemic, showed that media representation of public healthcare policies and measures excluively focused on only socialinstitutional system (Abbas, 2020;Abbasi, 2020;Chen et al, 2022;Xu et al, 2022). For example, the TV media coverage of political power structures of race was far more than that of physical outcomes during the first stage of the pandemic in the United States (Xu et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity of media coverage matters, but not as much as other factors such as public opinion, emotions, the pollution's physical qualities, the economy, and location (7,(16)(17)(18)(19)(20)(21)(22). Based on the message's substance and phrasing, the credibility of the information provider, and the characteristics of the audience, media coverage can either increase or decrease public support for aggressive action against COVID (23). The emerging infectious illnesses represent a significant threat to human life and are extremely challenging to contain, making the rising frequency of public health catastrophes involving them a noteworthy issue (24).…”
Section: Introductionmentioning
confidence: 99%